(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
Researching the waist support belt becomes more important. It’s said that the waist support belt can help pregnant women to relieve pregnancy-related pain, but the function of support belt couldn’t be unanimously identified by studies or clinical trials’ confirm at present. In this paper, the force analysis model is established, aiming to detect the role of the waist support belt. Aiming at the dressing effect is not prominent, when pregnant women just wear the waist support belt. In the paper, analyzing the pain causes of the pregnant women’s waist by the theory of mechanics is the basis of research. Through force analysis, it is effective to know how the support belt plays the role. Then, data by pressure test is used to understand the effect, if the support belt can relieve the waist pain of pregnant women. The result is used to verify the results of force analysis. And the data of pressure can explain its functionality. It provides a evaluation method of waist support belt through force analysis and pressure test.